Simulation and experimental validation of magnetic nanoparticle accumulation in a bloodstream mimicking flow system - Reinelt, Magdalena; Ahlfs, Johannes; Stein, René; Alexiou, Christoph; Bänsch, Eberhard; Friedrich, Ralf P.; Lyer, Stefan; Neuß, Maria; Neuß, Nicolas (Journal of Magnetism and Magnetic Materials, 2023)
In this paper, a mathematical model for the dynamics of superparamagnetic iron oxide nanoparticles (SPIONs) in a laminar flow through a pipe under the influence of an external magnetic field of a single electromagnet is derived. The model consists of a convection–diffusion equation coupled with magnetostatic equations. The accumulation of particles along the boundary is modeled with the help of a surface concentration. Based on experimental data describing the retention of lauric acid coated SPIONs in a tubular flow under the influence of a magnetic field, the model is parametrized and finite element simulations are performed. With the exception of one outlier at low SPION concentration and high flowspeed, the simulation results agree very well with the experimental measurements within the bounds of the measurement error.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Convection–diffusion equation; Finite element method (FEM); Magnetic drug targeting (MDT); Magnetic force on nanoparticles; Particle accumulation; Superparamagnetic nanoparticle (SPION)